2015
DOI: 10.1038/labinvest.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Cavin-1 and Caveolin-1 are both required to support cell proliferation, migration and anchorage-independent cell growth in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is a childhood soft tissue tumor with broad expression of markers that are typically found in skeletal muscle. Cavin-1 is a recently discovered protein actively cooperating with Caveolin-1 (Cav-1) in the morphogenesis of caveolae and whose role in cancer is drawing increasing attention. Using a combined in silico and in vitro analysis here we show that Cavin-1 is expressed in myogenic RMS tumors as well as in human and primary mouse RMS cultures, exhibiting a broad subcellular localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 103 publications
2
29
0
Order By: Relevance
“…Since Cavin‐1 and CAV‐1 always interrelated together and influenced each other, knocking down either Cavin‐1 or CAV‐1 is responsible for the decrease in expression of the other protein. Moreover, a recent study has shown that Cavin‐1 and CAV‐1 are both required for cell proliferation and migration in rhabdomyosarcoma and indicated that the cooperation between Cavin‐1 and CAV‐1 underlies the cell growth in myogenic tumors . In the present study, we found that decreased Cavin‐1 expression did not inhibit the CAV‐1 mRNA at the transcript level, which was confirmed using the Cavin‐1 knockout mice .…”
Section: Discussionsupporting
confidence: 85%
“…Since Cavin‐1 and CAV‐1 always interrelated together and influenced each other, knocking down either Cavin‐1 or CAV‐1 is responsible for the decrease in expression of the other protein. Moreover, a recent study has shown that Cavin‐1 and CAV‐1 are both required for cell proliferation and migration in rhabdomyosarcoma and indicated that the cooperation between Cavin‐1 and CAV‐1 underlies the cell growth in myogenic tumors . In the present study, we found that decreased Cavin‐1 expression did not inhibit the CAV‐1 mRNA at the transcript level, which was confirmed using the Cavin‐1 knockout mice .…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, CAV1 was found to be overexpressed in cancers of liver, colon, breast, kidney, lung, among others [29], and acts as a tumour promoter or suppressor depending on tumour type and stage [23, 33]. Regarding its tumour promoting function, it has been reported that high expression of CAV1 drives tumourigenesis by inhibiting apoptosis, facilitating anchorage-independent growth, drug resistance as well as metastasis [30, 3339]. For instance, CAV1 expression in liver cancer patients was found to positively correlate with differentiation status, increased portal vein invasion, intrahepatic metastasis, and to predict overall survival outcome [37].…”
Section: Relevance Of Caveolin-1 In Cancermentioning
confidence: 99%
“…In vitro studies were conducted using the human embryonal RD cells, RD12, RD18 and alveolar RH30 cells, as described in [50]; the primary mouse embryonal U57810 and alveolar U23674 cultures were derived from transgenic mice in which either p53 loss or concomitant p53 loss and Pax3-Foxo1 knock-in was restricted to Myf6 (myogenic factor 6)-positive myoblasts, respectively [53, 54]. Cells were routinely maintained under standard conditions (37°C and 5% CO 2 in humidified incubator) in a growth medium (GM), consisting of high-glucose Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 100 μg/ml penicillin—streptomycin antibiotics; RH30 cells also received 1% L-Glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…Lack or improper function in some of these protein members have been reported to affect caveolar function, hence disturbing the whole body homeostasis and contributing significantly in the onset and/or progression of diseases like diabetes, muscular dystrophies and cancer [44, 45]. We [4648] and others [49] have previously documented the expression of Caveolins in RMS and more recently shown the important contribute of Cav-1 and Cavin-1 on tumor growth [48, 50]. In this work we have investigated whether Muscle-Restricted Coiled-coil (MURC)/cavin-4, a plasma membrane and Z-line associated protein exhibiting an overlapping distribution with Cav-3 in heart and muscle tissues [51, 52], may be expressed and play a role in RMS.…”
Section: Introductionmentioning
confidence: 99%